Delimitação e avaliação em distritos de inovação em saúde: o caso de viva@porangabussu - Cavalcante, Teana da Silveira (2023)
The research is based on information modeling and the use of data for planning. Its scope is around the Porangabussu campus, Fortaleza, Ceará, Brazil and considers the implementation of a Health Innovation District – DIS in the region. The Health Innovation District (DIS) aims to create an environment more conducive to new solutions not only in health, but also in urban planning, education and citizenship issues. The proposition of innovation districts presents itself as a strategy for urban and sustainable renewal , aimed at compact cities. The ongoing work relevant to the line of urban planning and information design proposes to investigate a device that not only allows identifying urban needs and needs through a quality indicator, but also the delimitation of the most viable region for the practice of innovation in health. It uses as a research hypothesis that through “City Information Modeling” (CIM), it is possible to recognize patterns and determining behaviors to delimit and evaluate the Porangabussu Health Innovation District. The formalization of the study is based on the concepts (1) of Hillier and Hanson's (1984) spatial syntax - which describes urban ordering and public-private relations through quantitative analyzes elucidating urban characteristics such as accessibility and land use; (2) “Spatial Capital” by Marcus (2007; 2010; 2019) - which constitutes a process of measuring variations in urbanity as a socio-spatial category, seeking to assess how accessible that local diversity can be to the city; (3) and iCam 2.0, a walkability index proposed by the Institute for Transport and Development Policies (ITDP Brasil, 2019). And as a result, a device capable of delimiting viva@porangabussu and establishing comparative parameters for environments is expected.